Stones of empire - Morris, Jan (Oxford University Press, 2005)
No empire in history built so variously as the British empire in India. The buildings there attest to the richness of an imperial presence that lasted--from the first trading settlement to the end of the Raj--some three hundred years. The attitude of the British to India was compounded partly of arrogance, but partly also of homesickness, and it shows in their constructions. Georgian terraces were adapted to tropical conditions, Victorian railway stations were elaborately orientalized, seaside villas were adjusted to suit Himalayan conditions, and everywhere the fundamental ambivalence of the British empire, a baffling mixture of good and evil, was mirrored in the imperial architecture